Social Group Related Entry Participation Motivations for Continuing Professional Development Activities Among Malaysian Registered Quantity Surveyors - Ariffin, Mohd Hisham; Torrance, Johan Victor (Penerbit Universiti Sains Malaysia, 2018)
Continuing Professional Development (CPD) is aimed at continually updating Malaysian quantity surveying professionals’ knowledge to help them adapt to changes and challenges in the Malaysian construction industry. Proof of such participation is now a condition for the renewal of quantity surveying practice licences with the Board of Quantity Surveyors Malaysia. This article describes the findings of the qualitative research phase of a research into CPD entry participation motivations of Malaysian registered quantity surveyors. The analysis method of the interview transcripts of 31 registered quantity surveyors combined content analysis and grounded theory analysis. This analysis generated seven motivation themes regarding participation in CPD activities. The influence of the social group underlie five of these motivation themes, that are professional and geographical isolation, professional belonging, ''balancing'' of obligations, racial group orientations, and social participation in voluntary associations. It is proposed that further research in group influences on entry participation motivations for CPD activities be done